The Effectiveness of Virtual Learning on English Speaking Skill for Students of Information System Program - Arumsari; Saly Kurnia Octaviani (Surakarta English and Literature Journal, 2021)
Educational institutions have implemented online distance learning and teaching since the COVID-19 pandemic in Indonesia around March 2020. This research was conducted to find the effectiveness and its factors of virtual learning on English speaking skills in the early of pandemic. This study was a descriptive qualitative. This research was conducted at STMIK Sinar Nusantara Surakarta in Central Java. The time of research was started from April until June 2020 and it was conducted for Second-semester students in the academic year of 2019/2020 with 50 students for the number of populations from Information System program. For the research findings, virtual learning was not effective in grammar and fluency aspects and it was less effective in accent and vocabulary aspects for second-semester students of Information System program. Some factors have occurred in those lack of effectiveness, such as, the limitation of time in presenting speaking skill, the inefficiency of lecturer in correcting the students’ accent directly, difficulties of students in understanding material, limitations of English students’ vocabularies, and tendency of students’ speaking presentation based on the textbook.